Climate Actions in the Face of Severe Drought: The Case of Rural Coastal Communities in Central Chile; [Acciones Climáticas Frente a la Sequía Severa: El Caso de Comunidades Rurales Costeras del Chile Central] - Reyes-Garcia, P; Jofre-Leiva, D (FLACSO Ecuador, 2024)
This research aims to understand and describe perceptions and actions of rural inhabitants challenged by severe drought and climate change affecting Chile’s central areas. It considers the cases of Santa Julia and Valle Alegre, two rural communities within the coastal city of Quintero. This area is inhabited by family agricultural households impacted by drought conditions in the last decades and close to several polluting industries. The analysis is based on the sense-making theoretical model to explain the problems that affect people’s everyday lives and their attempts to solve them by means of information produced with their own resources, within their communities and with the support of state and private agents. Between November and December 2021, the authors carried out in-depth interviews with 13 informants from both communities. The research findings suggest that severe drought leads to discontinuities both in their productive activities and community and family ties. In their search for solutions, both communities struggle with weak social bonds when attempting to organize collective action. Furthermore, they distrust local companies’ and neighbors’ help. People thus feel insecure about the future and hope that seasonal rains eventually return. In the meantime, they try to adapt and mitigate environmental impacts with the help of some public and international institutions and the application of agricultural innovations. © 2024 FLACSO Ecuador. All rights reserved.